Becoming Muslim - McGinty, A. Mansson. author. aut Link
VIII, 208 p.
Keywords: While Islam has become a controversial topic in the West, a growing number of Westerners find powerful meaning in Islam. Becoming Muslim is an ethnographic study based on in-depth interviews with Swedish and American women who have converted to Islam.